Virulence and pathogenicity of group B Streptococcus: Virulence factors and their roles in perinatal infection - Christina J. Megli; Sophia M. Carlin; Elizabeth J. Giacobe; Gideon H. Hillebrand; Thomas A. Hooven (Virulence)
This review summarizes key virulence factors associated with group B Streptococcus (GBS), a significant pathogen particularly affecting pregnant women, fetuses, and infants. Beginning with an introduction to the historical transition of GBS from a zoonotic pathogen to a prominent cause of human infections, particularly in the perinatal period, the review describes major disease manifestations caused by GBS, including sepsis, meningitis, chorioamnionitis, pneumonia, and others, linking each to specific virulence mechanisms. A detailed exploration of the genetic basis for GBS pathogenicity follows, emphasizing the roles of capsules in pathogenesis and immune evasion. The paper also examines the molecular structures and functions of key GBS surface proteins, such as pili, serine-rich repeat proteins, and fibrinogen-binding proteins, which facilitate colonization and disease. Additionally, the review discusses the significance of environmental sensing and response systems, like the two-component systems, in adapting GBS to different host environments. We conclude by addressing current efforts in vaccine development, underscoring the need for effective prevention strategies against this pervasive pathogen.